A Study on Commercial Vehicle Speeds and Its Operational Characteristics - Ho, J.S.; Abdul Manan, M.M. (Journal of the Society of Automotive Engineers Malaysia, 2021)
A commercial vehicle is the backbone of the logistics industry which drives a vibrant economy of a country. Nevertheless, commercial or heavy vehicle-related accident is drawing serious attention. The height, weight and width dimension of the commercial vehicles reduce the visibility of other drivers and thereby increase the risk of an accident. Furthermore, due to the evolution of technology, larger trucks are now equipped with higher horsepower where a lot of speeding-related accidents were reported. This study is set to evaluate the speed profile for different types of commercial vehicles at different road hierarchy. The results indicate that in general most of the heavy vehicles (4.39%-98.61%) travelled fast and did not comply with the speed limits posted on different types of road hierarchy. The lower the posted speed limit the higher the percentage of non-compliance rates which means that the compliance increase as the speed limit increase. The majority of the commercial vehicles (28%-57%) occupied the middle lanes and those smaller sizes of vehicles (as compared to other sizes of commercial vehicles) had more tendencies to travel on the fast lane.